Keg wine technology as a service innovation for sustainability in the foodservice industry. (1st August 2022) - Pougnet, Stéphanie; Martin-Rios, Carlos; Pasamar, Susana
Abstract: Keg wine technology that allows for more sustainable packaging and distribution of wine is an innovation launched in the otherwise conservative wine industry. Yet, the study of keg wine through the lenses of sustainable offering in services is daunted by the challenges around sustainability innovation in service providers. Drawing on the sustainability-oriented service innovation (SOSI) tool (Calabrese et al., 2018a, 2018b ), this paper uses keg wine as a case study of the forces that drive or hinder the adoption of sustainability innovation in service activities like foodservice. Data from owners and general managers of Swiss foodservices provides initial insight into the perceived benefits and challenges for the adoption of innovations with sustainability potential. Specifically, results show that the willingness to adopt keg technology increases when potential long-term sustainability benefits are paired with new business interactions and new delivery systems. The study offers insights that could be used whether a restaurant is adopting innovative keg wine or not, especially as sustainability is an increasingly determinant driver of customer purchase behavior. Highlights: Keg wine technology and packaging is a service innovation for sustainability in foodservice. SOSI forces driving willingness to adopt keg wine technology are new business interactions and new delivery systems. Sustainability innovation offers insights for the willingness to adopt keg wine. Foodservices should inform their customers about the sustainability benefits of keg wine as SOSI.